Clientelism, public goods provision, and governance - Maria C. Lo Bue; Kunal Sen; Staffan I. Lindberg (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
It is widely believed that clientelism-the giving of material goods in return for electoral support-is associated with poorer development outcomes. However, systematic cross-country evidence on the deleterious effects of clientelism on development outcomes is lacking. In this paper we examine the relationship between political clientelism, public goods provision, and governance quality using cross-country panel data for 161 countries for the period 1900-2017. We distinguish between two manifestations of political clientelism-whether vote buying exists, and whether political parties offer material goods to their constituents in exchange for political support (non-programmatic party linkages). We find negative effects of political clientelism on development outcomes, with increases in clientelism leading to lower coverage of welfare programmes, increased political corruption, and weaker rule of law. We also find that the deleterious effects of political clientelism are mainly through non-programmatic party linkages rather than the practice of vote buying.
Keywords: D72; H40; H53; O10; 330; political clientelism; development; welfare programmes; corruption